Turkey : Third and Fourth Reviews Under the Stand-By Arrangement and Request for Waiver of Performance Criteria-Staff Report; Staff Supplement, Press Release on the Executive Board Discussion; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report, 2006)
Although Turkey's economic performance has been strong, growing external imbalances exposed the country to a reversal of sentiment. In the wake of recent market turbulence, the authorities have recommitted to strong policies and stepped up program implementation. The authorities' commitment to tighter fiscal policy will help preserve market confidence and resume disinflation. These delays are wide ranging, including on the landmark pension reform, tax reform, bank supervision, and state bank privatization. Political developments added to market concern, and discussions focused on the appropriate monetary policy response.